Robust Association Between Changes in Coronary Flow Capacity Following Percutaneous Coronary Intervention and Vessel-Oriented Outcomes and the Implication for Clinical Practice - Hamaya, Rikuta; Yonetsu, Taishi; Sayama, Kodai; Matsuda, Kazuki; Ueno, Hiroki; Nagamine, Tatsuhiro; Misawa, Toru; Hada, Masahiro; Hoshino, Masahiro; Sugiyama, Tomoyo; Sasano, Tetsuo; Kakuta, Tsunekazu (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary flow capacity (CFC) is a potentially important physiologic marker of ischemia for guiding percutaneous coronary intervention (PCI) indication, while the changes through PCI have not been investigated. Objectives To assess the determinants and prognostic implication of delta CFC, defined as the change in the CFC status following PCI. Materials and Methods From a single-center registry, a total of 450 patients with chronic coronary syndrome (CCS) who underwent fractional flow reserve (FFR)-guided PCI with pre-/post-PCI invasive coronary physiological assessments were included. Associations between PCI-related changes in thermodilution method-derived CFC categories and incident target vessel failure (TVF) were assessed. Results The mean (SD) age was 67.1 (10.0) years and there were 75 (16.7%) women. Compared with patients showing no change in CFC categories after PCI, patients with category worsened, +1, +2, and +3 category improved had the hazard ratio (95% CI) for incident TVF of 2.27 (0.95, 5.43), 0.85 (0.33, 2.22), 0.45 (0.12, 1.63), and 0.14 (0.016, 1.30), respectively (p for linear trends = 0.0051). After adjustment for confounders, one additional change in CFC status was associated with 0.61 (0.45, 0.83) times the hazard of TVF. CFC changes were largely predicted by the pre-PCI CFC status. Conclusion Coronary flow capacity changes following PCI, which was largely determined by the pre-PCI CFC status, were associated with the lower risk of incident TVF in patients with CCS who underwent PCI. The CFC changes provide a mechanistic explanation on potential favorable effect of PCI on reducing vessel-oriented outcome in lesions with reduced CFC and low FFR.